Quantifying commuter exposures to volatile organic compounds - Kayne, Ashleigh, author; Volckens, John, advisor; Peel, Jennifer, committee member; Collett, Jeffrey L., committee member (Colorado State University. Libraries, 2014)
Motor-vehicles can be a predominant source of air pollution in cities. Traffic-related air pollution is often unavoidable for people who live in populous areas. Commuters may have high exposures to traffic-related air pollution as they are close to vehicle tailpipes. Volatile organic compounds (VOCs) are one class of air pollutants of concern because exposure to VOCs carries risk for adverse health effects. Specific VOCs of interest for this work include benzene, toluene, ethylbenzene, and xylenes (BTEX), which are often found in gasoline and combustion products. Although methods exist to measure time-integrated personal exposures to BTEX, there are few practical methods to measure a commuter's time-resolved BTEX exposure which could identify peak exposures that could be concealed with a time-integrated measurement. This study evaluated the ability of a photoionization detector (PID) to measure commuters' exposure to BTEX using Tenax TA samples as a reference and quantified the difference in BTEX exposure between cyclists and drivers with windows open and closed. To determine the suitability of two measurement methods (PID and Tenax TA) for use in this study, the precision, linearity, and limits of detection (LODs) for both the PID and Tenax TA measurement methods were determined in the laboratory with standard BTEX calibration gases. Volunteers commuted from their homes to their work places by cycling or driving while wearing a personal exposure backpack containing a collocated PID and Tenax TA sampler. Volunteers completed a survey and indicated if the windows in their vehicle were open or closed. Comparing pairs of exposure data from the Tenax TA and PID sampling methods determined the suitability of the PID to measure the BTEX exposures of commuters. The difference between BTEX exposures of cyclists and drivers with windows open and closed in Fort Collins was determined. Both the PID and Tenax TA measurement methods were precise and linear when evaluated in the laboratory using standard BTEX gases. The LODs for the Tenax TA sampling tubes (determined with a sample volume of 1,000 standard cubic centimeters which is close to the approximate commuter sample volumes collected) were orders of magnitude lower (0.04 to 0.7 parts per billion (ppb) for individual compounds of BTEX) compared to the PIDs' LODs (9.3 to 15 ppb of a BTEX mixture), which makes the Tenax TA sampling method more suitable to measure BTEX concentrations in the sub-parts per billion (ppb) range. PID and Tenax TA data for commuter exposures were inversely related. The concentrations of VOCs measured by the PID were substantially higher than BTEX concentrations measured by collocated Tenax TA samplers. The inverse trend and the large difference in magnitude between PID responses and Tenax TA BTEX measurements indicates the two methods may have been measuring different air pollutants that are negatively correlated. Drivers in Fort Collins, Colorado with closed windows experienced greater time-weighted average BTEX exposures than cyclists (p: 0.04). Commuter BTEX exposures measured in Fort Collins were lower than commuter exposures measured in prior studies that occurred in larger cities (Boston and Copenhagen). Although route and intake may affect a commuter's BTEX dose, these variables are outside of the scope of this study. Within the limitations of this study (including: small sample size, small representative area of Fort Collins, and respiration rates not taken into account), it appears health risks associated with traffic-induced BTEX exposures may be reduced by commuting via cycling instead of driving with windows closed and living in a less populous area that has less vehicle traffic. Although the PID did not reliably measure low-level commuter BTEX exposures, the Tenax TA sampling method did. The PID measured BTEX concentrations reliably in a controlled environment, at high concentrations (300-800 ppb), and in the absence of other air pollutants. In environments where there could be multiple chemicals present that may produce a PID signal (such as nitrogen dioxide), Tenax TA samplers may be a better choice for measuring BTEX. Tenax TA measurements were the only suitable method within this study to measure commuter's BTEX exposure in Fort Collins, Colorado.
Keywords: PID; commuter exposures; VOC